Семантичне наповнення лінгвістичного символу кінь у біблійному тексті - Штибель, Юлія; Shtybel, Yulia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті простежено функціонування лінгвістичного символу кінь у біблійному тексті, розглянуто мовні засоби вираження словесних образів-символів коня (агенсні, пацієнсні поєднання слів, порівняльні та різновиди синтаксичних конструкцій, асоціативні ряди).The article traces the functioning of the linguistic symbol of the horse in the biblical text, scientific achievements in the field of linguistic studies of the biblical text have been defined, the comprehension of the linguistic symbol as a polysemantic and multiaspect objective-conceptual image in the semantic expression has been presented as the one that is located at the turn of interacting coordinate systems; linguistic means of expressing verbal symbols of the horse have been examined (agent- and patient-related word combinations, similies and a variety of syntactic structures, associative ranges). Dominant and peripheral image notions of the considered symbol have been clarified which gave the opportunity to identify their pragmatic, cognitive, archetypal,axiological parameters and its specificity.
The semantic content of the linguistic symbol of the horse in the biblical text
Keywords: символ; Біблія; номінативна модель; синтаксична конструкція; домінанта; периферія; symbol; Bible; nominative model; syntactic structure; derivative; dominant; periphery